Exact Solutions to the Sharma-Tasso-Olver Equation by Using Improved G′/G-Expansion Method - Yinghui He; Shaolin Li; Yao Long (Journal of Applied Mathematics)
This paper is concerned with a double nonlinear dispersive equation: the Sharma-Tasso-Olver equation. We propose an improved G′/G-expansion method which is employed to investigate the solitary and periodic traveling waves of this equation. As a result, some new traveling wave solutions involving hyperbolic functions, the trigonometric functions, are obtained. When the parameters are taken as special values, the solitary wave solutions are derived from the hyperbolic function solutions, and the periodic wave solutions are derived from the trigonometric function solutions. The improved G′/G-expansion method is straightforward, concise and effective and can be applied to other nonlinear evolution equations in mathematical physics.